2019
DOI: 10.21512/bbr.v10i3.5683
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Good Governance of Village Government Office in Sidoarjo

Abstract: This research examined determinant factors of good governance of a village government office in Sidoarjo. This research used a survey and a cross-section through a questionnaire as the data collection. The unit of analysis was the citizen who worked as a state civil apparatus and had used public services in a village government office. To determine the sample, the researchers used a simple random sampling. The data were analyzed using Structural Equation Modeling (SEM). The results show that the rule of law an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Several residents of Kajar Hamlet saw a large market potential for fresh tilapia products to form a group of tilapia farmers. Kajar Hamlet with the support of the Batu City Government and ITS in early 2022 received assistance and became the 4th teaching industry through the Pusat Kajian Kebijakan Publik, Bisnis dan Industri (PKKPBI) under the DRPM-ITS [4]. The concrete form of ITS support is to get 50 cages for tilapia cultivation along with tilapia seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Several residents of Kajar Hamlet saw a large market potential for fresh tilapia products to form a group of tilapia farmers. Kajar Hamlet with the support of the Batu City Government and ITS in early 2022 received assistance and became the 4th teaching industry through the Pusat Kajian Kebijakan Publik, Bisnis dan Industri (PKKPBI) under the DRPM-ITS [4]. The concrete form of ITS support is to get 50 cages for tilapia cultivation along with tilapia seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies h ave d e m o n s t ra te d t h a t i m p l e m e n t i n g effective governance practices in village public administration can effectively deter corruption and enhance the autonomy of village financial management (Putri et al, 2023;Susilowati et al, 2020). Other publications argue the importance of public involvement in organizing village governance (Handayani et al, 2023;Junaedi, 2023) and the efficacy of law enforcement (Ambarwati et al, 2019), as well as the collaboration and understanding between all relevant elements in the village (Pane, 2019). However, other research has shown that the implementation of good governance can also be abused and contraproductive in the case of China and Indonesia (Aminudin, 2019;Wang & Yuan, 2021).…”
Section: Public Policy Implementation With the Intersection Of Villag...mentioning
confidence: 99%
“…The results of the interview with the informant about the structuring of government administration in the field of public services as stated "the achievement of the effectiveness of the implementation of government administration in the field of public services including population services, socio-cultural services, general administrative services, development services, and licensing services". Thus, the effectiveness of the implementation of government administration in the field of public services includes population services, socio-cultural services, general administrative services, development services, and licensing services (Ambarwati et al, 2019).…”
Section: Field Of Public Servicementioning
confidence: 99%
“…Village officials who are also assigned duties in the field of administrative administration occupy a very important position because as the lowest government organ knows for sure all the conditions and problems that exist in their area, inputs to the sub-district government regarding various information and information are needed in making regional and national policies for the needs of overall development. Thus, village heads in carrying out their daily duties, especially those related to the presentation of the data and information needed, are increasingly required to have hard work and optimal abilities to facilitate the implementation of government tasks (Ambika et al, 2019).…”
Section: Administrative Sectormentioning
confidence: 99%